Specificity of early clinical-speech therapy for oral intake in premature infants with bronchopulmonary dysplasia - Červenková, Barbora (Logopedia Silesiana, 2020)
Oral food intake in premature infants has its own specificity, and this is especially true for children diagnosed with bronchopulmonary dysplasia (BPD). Respiratory diseases are one of the primary risks factors for the development of aversive eating behavior in early childhood. Eating difficulties in this group of children correlate with the severity of this diagnosis. This article provides an overview of the literature on the subject devoted to abnormalities of the motor component of sucking as well as coordination of sucking, swallowing and breathing (SPD) and specific clinical-speech therapy interventions suitable for children with BPD.